GeoRoma: il servizio cartografico unificato di Roma Capitale - Redazione MediaGEO (GEOmedia, 2025)
Introducing GeoRoma: A New Era for Spatial Data in the City of Rome. In a city as vast and multifaceted as Rome, managing territorial information is more than a technical challenge—it's a strategic priority. Over the past several years, the City Administration has undertaken a major effort to centralize and modernize its geospatial data infrastructure. The goal: to provide accessible, up-to-date, and interoperable geographic information to support public services, urban planning, and citizen engagement. This transformation has taken shape through the development of a modern WebGIS platform and the public release of new tools for accessing spatial data. Alongside the institutional Geoportal, the city has recently launched GeoRoma, a mobile application designed to make key geographic information available to users—citizens, professionals, and administrators alike—in an intuitive and location-aware format. Fully aligned with national and international standards, GeoRoma is already proving to be a powerful resource for navigating and understanding the city's complex geography. To learn more about the vision behind this initiative, we spoke with Engineer Daniele Condurso, the manager responsible for the development of the GeoRoma system.